Using Make A Match Method to Improve the Students’ Reading Comprehension at SMP Negeri 2 Bantaeng - Surya Annysa Litha; Syarifuddin Dollah; Amirullah Abduh (Journal of Excellence in English Language Education, 2023)
The objective of this research was to find out whether using the make a match method improves the students’ reading comprehension. This research took place at SMP Negeri 2 Bantaeng. The population of this research was the students of SMP Negeri 2 Bantaeng. The researchers used a simple random sampling technique. The instrument of this research was a reading test which was administered as a pre-test and post-test. Based on the result of the mean score, the researchers found the use make a match method can improve the students’ reading comprehension. It was proved by the result of the post-test which was higher than the result of the pre-test (60.60 > 76,40). The result of the t-test concluded that the students taught using the make a match method got better scores after treatment by using make a match method. Then, the researchers concluded that using make a match method can improve the students’ reading comprehension, especially in literal comprehension and inferential comprehension.